Prostate Cancer-Associated Disseminated Intravascular Coagulation with Excessive Fibrinolysis Treated with Degarelix - Shawn Y. Ong; Josephine Taverna; Clint Jokerst; Thomas Enzler; Emad Hammode; Elisa Rogowitz; Myke R. Green; Hani M. Babiker (Case Reports in Oncological Medicine)
Disseminated intravascular coagulation (DIC) with excessive fibrinolysis (XFL) is a rare and acute life-threatening variant of DIC in patients with prostate cancer. Patients present with coagulopathy, hypofibrinogenemia, and systemic bleeding. We describe a case of DIC XFL caused by prostate cancer (PC) successfully treated with a single injection of degarelix, a gonadotropin-releasing hormone (GnRH) receptor antagonist. This led to prompt control of the patient’s coagulopathy within ten days of treatment. Our case highlights features of this rare and devastating hemorrhagic complication of PC along with a fast-acting and effective therapeutic drug option.